Planning Models for Electricity Access : Where Do we Go from Here? - Srinivasan, Rahul; Chattopadhyay, Debabrata (World Bank, Washington, DC, 2020)
Well-integrated planning models can help cover the whole planning spectrum - from the national level down to granular distribution at the village level. Integration of models is critical to ensure that investment plans are realistic and accurately reflect the costs that utilities face in practice. The foregoing review of power system planning models and sophisticated stand-alone geographic information systems (GIS) - based models suggests the following questions: is there a need to bring the two paradigms closer? If so, do analytical frameworks exist to accomplish the task?